Diagnóstico do potencial olímpico de alunos de 15 a 17 anos da rede estadual de ensino de Cuiabá-MT - Fontes, José Henrique de Queiróz (2013)
Introduction: The school promotes the sport socialization process and integral education of citizens. Objective: This study aimed to diagnose potential Olympic schoolchildren from 15 to 17 years in the public schools of Cuiaba-MT. Method: This was a cross-sectional descriptive and exploratory, representative of the population of 28 schools with a total of 11.006 students (414 students: 229 boys and 185 girls from 25 schools). We applied tests of physical agility, speed, explosive strength of upper limbs, lower limbs explosive strength, abdominal strength and endurance generally classified by PROESP-BR. Data were categorized and distributed in percentages. Results: For the entire sample, the best results were obtained in tests of forward speed and explosive power of the lower limbs. Except for the speed test displacement most students had around reasonable performance and weak in the other five tests. The sample had the worst results in poor performance for agility (55.6%), abdominal strength (54.4%) and overall resistance (36.7%). Considering the sum of the tests had 24.0% boys and 18.5% girls classified as very good or excellent. Conclusion: The poor performance related to low-level motor sport is also associated with greater exposure to health problems. Apparently these students should be exposed to low levels of physical activity in the school environment, lacking investigate the quantity and quality of physical education classes in order to combat this.